Variasi Fonologis pada Bahasa Melayu Dialek Betawi di Kota Bekasi: Kajian Dialektologi - Dikhrish, Awfa; Sudana, Undang; Wiyanti, Sri (CV. Creative Tugu Pena, 2024)
Indonesia is a country that is rich in linguistic diversity. The richness of language in Indonesia has caused various language studies to emerge, one of which is dialectology. This research aims to describe phonological variations in Swadesh data at three observation points in Bekasi City, namely Aren Jaya Village, Bekasi Jaya Village, and Margahayu Village. The research method used is descriptive with a qualitative approach. The data used in this research is a list of 260 Swadesh vocabulary words with the three observation points mentioned. The data sources or informants for this research are native residents of the research area with the criteria being native speakers of the Betawi dialect of Malay, physically and mentally healthy, have normal speech organs, and the language age ranges from 25-65 years. Data collection in this research used the listening method and the skill method accompanied by note-taking techniques. The main instrument in this research is the Betawi dialect variations of Malay in the Swadesh vocabulary list totaling 260, and the supporting instrument is the researcher himself. The results of the research show that there are 36 glosses of Swadesh data which have phonological linguistic differences with descriptions of vowel variations and consonant variations. The next results are 18 glosses of vowel variations, and 20 glosses of consonant variations. This discrepancy in numbers will be explained in this study. The research results are presented in formal form. Keywords: Phonological Variations, Betawi Dialect, Dialectological Study